RISK FACTORS RELATED TO URINARY TRACT INFECTION IN HEALTH CARE - Maia, Francisco Eudison da Silva; Evangelista, Anne Itamara Benigna; Vieira, Alcivan Nunes (Journal of Health Care, 2015)
This research aimed to identify risk factors for the occurrence of urinary tract infection related to healthcare. It is an integrative literature review of articles published in Biblioteca Virtual em Saúde (BVS) fromApril to June 2012. The following descriptors were used: "sistema urinário", "bexiga urinária" and "fatoresde risco" ["urinary tract", "urinary blatter" and "risk factors"]. The main risk factors associated with urinarytract infection in health care are: prior pathological condition; hospitalization; indication of impropercatheterization; care of the catheter; the catheter dwell time; sex and age of patient. The catheterization isa major risk factor for the occurrence of the infection and generally the most remembered. However, thereare other factors that need to be taken into account by health professionals. By identifying these factors,professionals can take effective measures of prevention and control.
Keywords: Nursing; cross infection; intensive care units.